Women's Leadership: A Comparative Study between Fiqh Traditions and Contemporary Fatwa - Masithoh Masithoh; Rosiana Kholifah (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze Islamic views on women's and non-Muslim leadership through a comparative study between classical fiqh traditions and contemporary fatwas. Leadership in Islam is a crucial issue often debated, particularly regarding the roles of women and non-Muslims in government or public office. This research seeks to answer questions about the criteria for ideal leadership from an Islamic perspective and its relevance to modern socio-political contexts. Theoretical framework: The study is grounded in the theoretical framework of fiqh siyasah (Islamic political jurisprudence), emphasizing justice, public interest (maslahah), and representation as the foundations of leadership. The literature reviewed includes classical fiqh texts, Qur'anic exegeses, and contemporary fatwas. Literature Review: The literature review reveals a dynamic discourse on the leadership of women and non-Muslims, ranging from restrictive traditional views to more inclusive modern approaches. Methods: The research employs a qualitative methodology with a descriptive-analytical approach. Data were obtained from literature sources, including primary and secondary references related to leadership in Islam. A thorough analysis was conducted to identify the differences and similarities between traditional and modern perspectives. Results: The findings indicate that ideal leadership in Islam is not solely determined by religion or gender but by a leader’s ability to act justly and uphold the rights of all citizens. In the Indonesian context, a non-Muslim leader can align with the nation's ideals as long as they practice justice and maintain the balance of people’s rights. Conversely, a Muslim leader who acts unjustly and oppresses individual rights does not fulfill the criteria of Islamic leadership. Surah Al-Maidah verse 57 is often cited as the basis for prohibiting Muslims from selecting non-Muslim leaders; however, exceptions are made in emergencies, including the delegation of responsibilities to non-Muslims as representatives of the people. Implications: The implications of this study highlight the importance of prioritizing justice and competence as the main criteria for selecting leaders, whether in organizations or governments. Without fair and competent leadership, it is challenging for an organization or nation to function effectively. Novelty: The novelty of this research lies in its contemporary interpretation of Islamic leadership, where recent fatwas demonstrate greater flexibility in addressing modern socio-political dynamics. This study provides a fresh perspective, bridging Islamic values with the demands of the modern world.